Practical experience of Traditional Chinese Medicine nursing clinical teaching path in teaching of breast care nursing students (中医护理临床教学路径在乳腺科护生带教中的应用体会) - LIU Shanshan (刘姗姗); LIU Kexin (刘可欣); CHEN Hong (陈宏) (中西医结合护理)
As a key specialty of the hospital, the Department of Breast Diseases has one of the first Tradtitional Chinese Medicine (TCM) nursing clinics officially authorized by Beijing Administration of Traditional Chinese Medicine, and undertakes the task of clinical teaching and practice for nursing students from various colleges and universities every year. The TCM nursing clinical teaching path had been used in clinical teaching and practice, aiming to teaching the breast diseases characterized TCM nursing technology, presenting the unique characteristics of TCM, giving play to the specialty advantages, looking forward to the "integration of schools and departments" model. It is expected to provide reference for training excellent nursing talents with TCM nursing practice ability and promoting the high-quality development of TCM nursing. (医院乳腺科作为医院重点专科, 拥有北京市中医管理局首批正式授权建设的乳腺专科中医护理门诊, 每年承担各院校护生临床实习的带教任务。科室运用中医护理临床教学路径法带教, 教授乳腺科特色中医护理技术, 展现中医魅力, 发挥专科优势, 展望“院系合一”模式, 以期为培养具有中医护理实践能力的优秀护理后备人才, 推动中医护理事业高质发展提供参考。)